Seroprevalence Study: Antibodies To Hepatitis B Core Antigen Among Blood Donors In Chattogram (Journal of Chittagong Medical College Teachers' Association, 2026)
Background: Hepatitis B Virus (HBV) remains a major global health concern, particularly in regions with limited screening. Antibodies to the Hepatitis B core antigen (antiHBc) indicate past or ongoing infection and help identify potential carriers. This study aims to assess the seroprevalence of anti-HBc among HBsAg-negative blood donors in Chattogram.Materials and methods: This cross-sectional observational study included 100 voluntary blood donors who were screened for anti-HBc (IgM and IgG) and anti- HBs using Electrochemiluminescence Immunoassay (ECLIA) and Chemiluminescent Microparticle Immunoassay (CMIA) respectively.  Results: The results revealed that 21% of the HBsAgnegative  donors were positive for anti-HBc, indicating previous or ongoing hepatitis B virus (HBV) infection. Notably, 76.2% of the anti-HBc-positive individuals were negative for anti-HBs, suggesting a potential risk of HBV reactivation or occult infection. Homemakers had the highest anti-HBc positivity rate (25%) while students had the lowest (15.8%). Blood transfusion recipients (33.3%) and those with a history of surgery (30.8%) showed higher anti-HBc positivity rates compared to other risk factors. Unvaccinated individuals exhibited a higher anti-HBc positivity rate (26.3%) than vaccinated individuals (14.0.Prior blood donors accounted for 76.2% of all antiHBc-positive cases.Conclusion: These findings highlight the hidden burden of past HBV exposure among asymptomatic blood donors and emphasize the need for enhanced vaccination coverage, safe transfusion practices and the potential inclusion of anti-HBc testing in blood donor screening protocols to reduce the risk of occult HBV infections in endemic areas.JCMCTA 2025 ; 36 (2) :  7-12